2004
DOI: 10.1345/aph.1e018
|View full text |Cite
|
Sign up to set email alerts
|

An Insulin Infusion Protocol in Critically Ill Cardiothoracic Surgery Patients

Abstract: An insulin infusion protocol designed to achieve a goal blood glucose range of 80-150 mg/dL efficiently and significantly improved TGC in critically ill postoperative cardiothoracic surgery patients without significantly increasing the incidence of hypoglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
58
0
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(64 citation statements)
references
References 17 publications
(23 reference statements)
4
58
0
2
Order By: Relevance
“…Bandwidth can be matched to a specific TGC interval [8][9][10][11][12][13][14][15][16][17][18] (Fig. 5), here 80-110 mg/dl [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bandwidth can be matched to a specific TGC interval [8][9][10][11][12][13][14][15][16][17][18] (Fig. 5), here 80-110 mg/dl [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, POC results must be accurate, because the clinical team uses them for immediate decision making. The TGC ranges at the top were obtained from published papers (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The mark in the top interval represents mean glucose (138 mg/dl) in the study by Lazar et al [8].…”
Section: Discussionmentioning
confidence: 99%
“…However, many published TGC protocols follow similar insulin dosing regimens (21)(22)(23). Glucose values used for simulation were obtained with the AccuChek Inform glucose meter using arterial whole blood to dose the meters.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective randomized controlled trial 11 of 1548 surgical ICU patients, hospital mortality was reduced by 34% after an intravenous insulin protocol was introduced. Following this landmark study, various intensive insulin protocols aimed at achieving inpatient glycemic control in the ICU, 1,7,[12][13][14][15][16][17][18] including the medical ICU, 19,20 have been described. The optimal target range for blood glucose level in critically ill patients remains unclear.…”
mentioning
confidence: 99%
“…2,11,12,14,[20][21][22] Others prefer to use less stringent ranges for blood glucose (eg, 100-140 mg/dL) in order to minimize the risk for hypoglycemia but still prevent hyperglycemia. 1,7,16,19 Although the first randomized controlled trial showed that tighter glucose control (80-110 mg/dL) reduced morbidity and mortality, 11 or at least did not increase mortality, 20 the NICE-SUGAR multicenter study 23 recently showed that tight glucose control increased mortality and increased the risk of severe hypoglycemia among adults in the ICU. These conflicting results led to the recommendation to avoid lower glucose targets in critically ill adults.…”
mentioning
confidence: 99%